Accreditation and clinical outcomes: shorter length of stay after first-time hospital accreditation in the Faroe Islands. (22nd March 2022) - Bergholt, Maria Daniella; Von Plessen, Christian; Johnsen, Søren paaske; Hibbert, Peter; Braithwaite, Jeffrey; Valentin, Jan Brink; Falstie-Jensen, Anne Mette
Abstract: Background: The aim of accreditation is to improve quality of care and patient safety. However, studies on the effectiveness of accreditation on clinical outcomes are limited and inconsistent. Comparative studies have contrasted accredited with non-accredited hospitals or hospitals without a benchmark, but assessments of clinical outcomes of patients treated at hospitals undergoing accreditation are sparse. The Faroe Islands hospitals were accredited for the first time in 2017, making them an ideal place to study the impact of accreditation. Objective: We aimed to investigate the association between first-time hospital accreditation and length of stay (LOS), acute readmission (AR) and 30-day mortality in the unique situation of the Faroe Islands. Methods: We conducted a before and after study based on medical record reviews in relation to first-time accreditation. All three Faroese hospitals were voluntarily accredited using a modified second version of the Danish Healthcare Quality Programme encompassing 76 standards. We included inpatients 18 years or older treated at a Faroese hospital with one of six clinical conditions (stroke/transient ischemic attack (TIA), bleeding gastic ulcer, chronic obstructive pulmonary disease (COPD), childbirth, heart failure and hip fracture) in 2012–2013 designated 'before accreditation'or 2017–2018' after accreditation'. The main outcome measures were LOS, all-cause AR and all-cause 30-day mortality. We computed adjusted cause-specific hazard rate (HR) ratios using Cox Proportional Hazard regression with before accreditation as reference. The analyses were controlled for age, sex, cohabitant status, in-hospital rehabilitation, type of admission, diagnosis and cluster effect at patient and hospital levels. Results: The mean LOS was 13.4 days [95% confidence interval (95% CI): 10.8, 15.9] before accreditation and 7.5 days (95% CI: 6.10, 8.89) after accreditation. LOS of patients hospitalized after accreditation was significantly shorter [overall, adjusted HR = 1.23 (95% CI: 1.04, 1.46)]. By medical condition, only women in childbirth had a significantly shorter LOS [adjusted HR = 1.30 (95% CI: 1.04, 1.62)]. In total, 12.3% of inpatients before and 9.5% after accreditation were readmitted acutely within 30 days of discharge, and 30-day mortality was 3.3% among inpatients before and 2.8% after accreditation, respectively. No associations were found overall or by medical condition for AR [overall, adjusted HR = 1.34 (95% CI: 0.82, 2.18)] or 30-day mortality [overall, adjusted HR = 1.33 (95% CI: 0.55, 3.21)]) after adjustment for potential confounding factors. Conclusion: First-time hospital accreditation in the Faroe Islands was associated with a significant reduction in LOS, especially of women in childbirth. Notably, shorter LOS was not followed by increased AR. There was no evidence that first-time accreditation lowered the risk of AR or 30-day mortality.